Modal Ekonomi Judi Slot Sebagai Peningkatan Ekonomi Secara Cepat Mahasiswa - Citra Arafabiola Pramudhya Anggraeni; A. Zahid (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
The aim of this research is to see to what extent slot gambling games provide a rapid economic improvement for students at one of the universities in Tulungagung, by analyzing whether it is true that Tulungagung State University students use online slot gambling as a rapid improvement in the economy. economic capital. This research is a qualitative research with a phenomenological approach which aims to analyze in depth the slot gambling game which is used as a fast economic boost by students based on the students' own subjective experiences. The research results show that slot gambling games are part of the euphoria of revealing the dynamics of students' thinking following the flow of technological developments. The results of the analysis show the truth that Tulungagung students use slot gambling games to gain rapid economic improvement. They feel they see an opportunity to improve the economy in an easy and fast way by playing slot gambling in the midst of busy lecture activities. This is proven by the existence of economic encouragement in the form of a desire to ease the family's economy in meeting their living needs during college. This is reinforced by the friendship environment which is influenced by gambling as well as the mental burden of despair due to economic problems and boredom in lectures. This is not in line with reality, students who play slot gambling admit that they make more losses than profits. Changes in life and a significant increase in economic levels from slot gambling games are not often found among students.